The implementation of IEEE 1588 clock synchronization system based on FPGA - Boqun Zhao; Ning Wang (Fifth International Conference on Intelligent Control and Information Processing, 2014)
IEEE 1588 precise time synchronization protocol is based on Ethernet. It has very important application in the synchronization of industrial system. Based on the analysis of IEEE 1588 protocol and best master clock algorithm, this paper presents a design scheme using FPGA, DM9000 and DP83640. This design is a combination of hardware and software to achieve IEEE 1588 protocol. Verified by experiment, it is correct and meets the modern industrial Ethernet requirement for the high precision clock.